The Effect of an Online Injury Prevention Warm-Up Program on Selected Physical Fitness and Performance Factors in School Students Aged 14 to 16 - Soroush Fard, Zahra; Alizadeh, Mohammadhossein; Karimizadeh Ardakani, Mohammad (International Journal of Education and Cognitive Sciences, 2025)
Purpose: This study evaluated the effect of a six-week online injury prevention warm-up program on selected physical fitness and performance factors in school students aged 14 to 16. Methods and Materials: A total of 344 students (172 girls, mean age = 15.3 years; 172 boys, mean age = 15.0 years) enrolled in physical education classes were randomly assigned to either a control group (n = 86) or an experimental group (n = 86). The intervention targeted four outcome variables: static balance, dynamic balance, flexibility, and agility. Pre- and post-intervention assessments were conducted over six weeks. Data were analyzed using independent t-tests and the Mann–Whitney U test. Results: In boys, average percentage changes were as follows: static balance increased by 4.56%, dynamic balance by 1.12%, and flexibility by 5.07%, while agility decreased by 1.68%. In girls, static balance improved by 32.80%, dynamic balance by 1.21%, flexibility by 8.37%, and agility improved by 0.93%. Significant improvements were observed in dynamic balance and flexibility for both sexes, while agility significantly improved in girls and decreased in boys. Static balance significantly improved only in girls. Conclusion: The findings demonstrate that a structured, online injury prevention warm-up program is effective in enhancing several key aspects of physical fitness and performance in adolescents, particularly in girls. The program can be implemented as an accessible and practical intervention in physical education settings to improve student outcomes and reduce injury risk.